Android-Based Algorithm and Programming Learning Media Mobile Application - Yusuf Ramadhan Nasution (Sean Institute, 2021)
This research is a type of development research. The product development model adopts a software development model consisting of (1) Analysis of software requirements, (2) design, (3) writing code and (4) testing. Data collection techniques are done by observation, interviews and questionnaires. The testing phase is carried out with product validation by experts, testing on the first user (lecturer) and testing on the end user (student).